2020
DOI: 10.1021/acsanm.0c01830
|View full text |Cite
|
Sign up to set email alerts
|

Pd Nanoparticles Supported on N- and P-Co-doped Carbon as Catalysts for Reversible Formate-Based Chemical Hydrogen Storage

Abstract: Efficient and reversible hydrogen-storage systems derived from liquid organic compounds are promising alternatives for sustainable energy supplies. Here, we report a Pd nanoparticle catalyst supported on porous carbon co-doped with nitrogen and phosphorous for reversible formate-based chemical hydrogen storage. The materials showed good catalytic performance for both formate dehydrogenation and bicarbonate hydrogenation. The N,P-dual-doped carbon was fabricated by directly pyrolyzing a mixture of 1,10-phenanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…For example, Shao et al prepared Pd supported on N-and P-co-doped carbon (Pd@ N,P−C) as a catalyst for reversible formate-based chemical hydrogen storage, and a significant higher activity of Pd@N,P− C was observed than those of Pd@C, Pd@NC, and Pd@PC, resulting from the donation of electrons from N and P in the carbon support to Pd. 30 However, such a prevalent codoping method for catalyst modification is rarely tested in the ligninfirst depolymerization. The resulting finer metal particles from codoping of carbon-based support are supposed to favor the reductive stabilization of the intermediates from the lignin-first depolymerization, and an introduction of acidic sites from some elements with a smaller electronegativity than carbon (e.g., P) is also likely to promote the release of lignin from biomass as well as the catalytic solvolysis of the β-O-4 linkages in lignin.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Shao et al prepared Pd supported on N-and P-co-doped carbon (Pd@ N,P−C) as a catalyst for reversible formate-based chemical hydrogen storage, and a significant higher activity of Pd@N,P− C was observed than those of Pd@C, Pd@NC, and Pd@PC, resulting from the donation of electrons from N and P in the carbon support to Pd. 30 However, such a prevalent codoping method for catalyst modification is rarely tested in the ligninfirst depolymerization. The resulting finer metal particles from codoping of carbon-based support are supposed to favor the reductive stabilization of the intermediates from the lignin-first depolymerization, and an introduction of acidic sites from some elements with a smaller electronegativity than carbon (e.g., P) is also likely to promote the release of lignin from biomass as well as the catalytic solvolysis of the β-O-4 linkages in lignin.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Codoping is usually on the coupling of N with another heteroatom (e.g., B, Cl, O, S, P), and codoping can further improve the efficiency of the reaction. N binds to metal atoms with strong affinity, and thus, it is not easy to tune the metal sites by changing the N and C coordination, which has some limitations, including metal aggregation and low metal loading . However, the doping of secondary heteroatoms with different atomic sizes and electronegativities can further improve the M–N–C structure (M stands for metal, e.g., Pd, Pt) to obtain higher catalytic activity of HDO.…”
Section: Heteroatom Codoped Carbon Catalysts For Biomass Hdomentioning
confidence: 99%
“…In addition to applications in environmental and energy areas, metal/N,P codoped carbon catalysts are known catalysts. As shown in Figure , Shao et al reported a Pd loaded N,P-dual-doped carbon catalyst (Pd/NPC). The materials show excellent catalytic performance in the hydrogenation of the bicarbonate.…”
Section: Heteroatom Codoped Carbon Catalysts For Biomass Hdomentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, P-doped carbon has been prepared from an organic phosphorous source, phosphoric acid, and P 2 O 5 , which needs to consume energy for calcination. [24][25][26] In addition, the conventional preparation processes are complicated for P-doped carbon supported catalysts. The present SPC method provides a simple, fast, and energy saving method for the preparation P-doped carbon-based materials.…”
mentioning
confidence: 99%